Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Global Television Formats in Africa: Localizing Idol - Nkosi Ndlela, Martin (Global Television Formats: Understanding Television Across Borders, 2012)
During the last decade, popular television formats have been replicated across the globe for local or regional consumption as program imports, adaptations, clones or imitations, raising questions on the possible ramiﬁcations of such cultural inﬂows. For Africa the international program ﬂow and the inﬂuence of Western media content has been a contentious issue for decades, underlying the cultural imperialism thesis of the 1970s and 1980s, and the centre– periphery paradigms which conceptualized the series of dependency relationships. In African media research concepts like cultural colonialism, media imperialism, neocolonialism, Americanization, homogenization, have been used to denote the unequal ﬂow and inﬂuence of Western media products in Africa. Within the framework of media globalization some scholars have even propounded a scenario of the emergency of a global culture mediated by the dominant Western media. The central issues in African media discussions have mainly revolved around the ﬂow of ﬁnished media programs and their perceived detriment to local cultures and identities. What is missing in the African research literature is the attention to television formats, a phenomenon described by Keane et al. (2002) as a vehicle for localization, since what is imported is not the content itself, but a recipe for creating a local version. Global reality format shows thus create a new picture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); Ghana (corpus analysé); Nigéria (corpus analysé); Norvège (lieu de production du savoir); _Nettoyé